2017
DOI: 10.1016/j.immuni.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Cells in the Central Nervous System

Abstract: The central nervous system (CNS) and its meningeal coverings accommodate a diverse myeloid compartment that includes parenchymal microglia and perivascular macrophages as well as choroid plexus and meningeal macrophages, dendritic cells, and granulocytes. These myeloid populations enjoy an intimate relationship with the CNS, playing an essential role in both health and disease. Although the importance of these cells is clearly recognized, their exact function in the CNS continues to be explored. Here we review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
225
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(237 citation statements)
references
References 180 publications
4
225
0
Order By: Relevance
“…Studies have shown that, although microglial cells play a major role in brain surveillance, perivascular macrophages represent a crucial immune regulator and sensor of perturbations in the CNS and periphery. These cells are derived from the bone marrow and are intimately associated with the bloodstream since they reside between EC and astrocyte end feet [72][73][74]. This privileged location of the perivascular macrophages allows them to simultaneously monitor the blood and the brain interstitial fluid, providing a fine control of brain homeostasis and BBB integrity [72,75].…”
Section: The Intimate Relationship Between the Central Nervous Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that, although microglial cells play a major role in brain surveillance, perivascular macrophages represent a crucial immune regulator and sensor of perturbations in the CNS and periphery. These cells are derived from the bone marrow and are intimately associated with the bloodstream since they reside between EC and astrocyte end feet [72][73][74]. This privileged location of the perivascular macrophages allows them to simultaneously monitor the blood and the brain interstitial fluid, providing a fine control of brain homeostasis and BBB integrity [72,75].…”
Section: The Intimate Relationship Between the Central Nervous Systemmentioning
confidence: 99%
“…In the physiological condition, studies have observed the presence of monocytes in meningeal spaces, although more evidence is still needed [82]. Granulocytes (i.e., neutrophils, mast cells, eosinophils, and basophils) can be found in meningeal spaces with mast cells also present in brain parenchyma [72,83]. These cells are highly phagocytic and play important roles in response to brain infections and tissue damage [72,84,85].…”
Section: The Intimate Relationship Between the Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Meantime, nanoparticles can be drained from tissues by lymphatics and they can be phagocytosed by subcapsular macrophages which exist in the draining lymph nodes; this can then be presented to adaptive immune cells, such as T cells, to mount an immune response in the brain. Alternatively, meningeal macrophages might uptake nanoparticles and modulate the meningeal immune response …”
Section: Discussionmentioning
confidence: 99%
“…Microglia, which are considered the primary APC in the brain microenvironment, serve as tissue-resident macrophages and may adapt to become perivascular macrophages that aid in tumor proliferation, invasion, and angiogenesis to create a more favorable tumor microenvironment (TME) (9,10). It has been shown that microglia have the potential to differentiate into the M1-like or M2-like macrophages to induce a pro-inflammatory (TNFα/IFNÎł response) or pro-tumoral (IL-4/TGFÎČ response) phenotype, respectively (11).…”
Section: Targeting Brain Metastasis With Cancer Immunotherapymentioning
confidence: 99%